Overview of the Content of Bisphenol A in the Amniotic Fluid of Pregnant Women And Its Adverse Health Outcomes - Dardan Dreshaj 1 , Flaka Pasha2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: This review represents a critical and constructive analysis of literature in the content ofBisphenol A in amniotic fluid of pregnant women and its adverse health outcomes. The review is generatedthrough summary, classification, analysis and comparison of already existing material and researches onfield.Methods : Databases as Scopus, PubMed, Medline, Web of Science, Global Health, were used to extractdata for the review. Search terms like “Bisphenol A”, “pregnancy”, “amniotic fluid”, “endocrine disruptors”were used. Out of 200 research articles screened, 70 most relevant studies are included in this review.Conclusions: This review highlights the correlation between Bisphenol A and its endocrine disruptingpotential, impacting especially fragile categories as pregnant women and their fetuses through itstoxicokinetic features and its metabolites. Thus, BPA distorts important physiological processes necessaryfor fetal development and disease progression later in life.We can conclude that human exposure to BPA, as one of the leading environmental contaminants, representsa major global issue and its adverse health outcomes can be debilitating for human health. Further researchon field considering BPA distribution, varying exposure rates, racial disparities, inter-species differences andEDCs cumulative effects, should be conducted. Finding safer alternatives for replacing BPA in market mustremain a priority.